Multiproxy approach to reconstruct fossil primate feeding behavior: Case study for macaque from the Plio-Pleistocene site Guefaït-4.2 (eastern Morocco) - Ramírez-Pedraza, Iván; Martínez, Laura M.; Aouraghe, Hassan; Rivals, Florent; Tornero, Carlos; Haddoumi, Hamid; Estebaranz-Sánchez, Ferran; Rodríguez-Hidalgo, Antonio; van der Made, Jan; Oujaa, Aïcha; Ibáñez, Juan José; Mhamdi, Hicham; et al. (Frontiers in Ecology and Evolution, 2023)
The genus Macaca belongs to Cercopithecidae (Old World monkeys), Cercopithecinae, Papionini. The presence of Macaca in North Africa is well known from the Late Miocene to the Late Pleistocene. However, the diet of fossil Macaca has been poorly described in the literature. In this study, we investigated the feeding habits of Macaca cf. sylvanus (n = 4) from the Plio-Pleistocene site Guefaït-4.2 in eastern Morocco through multiproxy analysis combining analyses of stable carbon and oxygen isotopes from tooth enamel, buccal microtexture, and low-magnification occlusal dental microwear. For both microwear analyses, we compared the macaques with a new reference collection of extant members of Cercopithecoidea. Our occlusal microwear results show for the fossil macaque a pattern similar to the extant Cercocebus atys and Lophocebus albigena, African forest-dwelling species that are characterized by a durophagous diet based mainly on hard fruit and seed intake. Buccal microtexture results also suggest the consumption of some grasses and the exploitation of more open habitats, similar to that observed in Theropithecus gelada. The δ13C of M. cf. sylvanus indicates a C3 based-diet without the presence of C4 plants typical of the savanna grassland in eastern Africa during this period. The high δ18O values of M. cf. sylvanus, compared with the contemporary ungulates recovered from Guefaït-4.2, could be associated with the consumption of a different resource by the primate such as leaves or fresh fruits from the upper part of trees. The complementarity of these methods allows for a dietary reconstruction covering a large part of the individual’s life.